Feasibility of parathyroid gland autofluorescence imaging after indocyanine green fluorescence angiography - Richard, Marieke; Rizo, Philippe (Frontiers in Endocrinology, 2023)
In thyroid surgery, autofluorescence allows the parathyroid glands (PTGs) to be located very early to protect them. Moreover, indocyanine green (ICG) fluorescence angiography (ICG-FA) allows for assessing the viability of the PTGs and identifying blood vessels to preserve them. The main limitation of using ICG-FA is that once ICG has been injected, it is no longer possible to observe PTG autofluorescence using existing devices. This study aimed to describe an approach that allows for visualization of the PTGs by autofluorescence, even after ICG injection.We redesigned the FLUOBEAM ® LX system to excite fluorescence at 685 nm and detected fluorescence between 700 and 900 nm. This device had short-pass filters at 775 nm that helped to split the contributions of the PTG autofluorescence and ICG fluorescence. Tests were performed on extemporaneous PTG preparations placed next to ICG droplets to assess for rejection of the ICG signal.Results: A low-pass filter at 775 nm detected 60% of the autofluorescence signals and 10% of the ICG signals.These findings support the possibility of visualizing PTG autofluorescence despite multiple ICG injections and measuring the balance between ICG and autofluorescence signals.ICG (25 mg) was purchased from Diagnostic Green (Indocyanine Green for Injection Kit, 25 mg). Bovine Serum Albumin was purchased from Sigma Aldrich (Bovine Serum Albumin, 5%; reference A4628-20ML). We performed fluorescence spectrometry measurements of ICG diluted with albumin at an excitation wavelength of 685 nm. We observed that the fluorescence yield was 30-50% lower than that measured at an excitation wavelength of 750 nm. The detection was performed on a larger